Exploring the Lived Experience of Missed Nursing Care in Postgraduate Nursing Students in Iran - Fatemeh Najafi; Alireza Nikbakht Nasrabadi; Leila Mardanian-Dehkordi (Shiraz University of Medical Sciences, 2021)
Background: Missed care is a global phenomenon, which can include many clinical conditions thatthreaten the patients' safety in all countries and cultures, and also indicates the quality of nursing care.The nursing students' awareness and understanding of missed nursing care is of great importance. Thecurrent study aims to explore the lived experience of postgraduate nursing students in missed care.Methods: The current qualitative study was performed based on the interpretive phenomenologicalapproach in Tehran, Iran, in February to December 2019. A total of 10 master's degree nursing studentswere selected through purposive sampling. A total of 10 semi-structured individual interviews wereused to collect the data. The trail version of MAXQDA-10 software was used for coding. All interviewswere recorded and codified, and the main themes were extracted from them using Dicklemann et al.'s(1989) analytical method.Results: Two main themes, five sub-themes, and 31 meaning units were obtained. The main themesincluded: "unfulfilled care" and "living in limbo".Conclusion: Missed care, as unfulfilled care, is accompanied with living in limbo for nursing students,and this condition is influenced by organizational and personal factors. It seems that managers canprevent missed nursing care by supervising nursing care, reducing the nurses' workload, creating asense of commitment to work, and enforcing ethical issues among nurses.